Differences in Executive Functions in Minors Suffering Physical Abuse and Neglect - Moreno-Manso, Juan Manuel (Journal of interpersonal violence, 2022)
This research analyzes the executive functions in minors between 7 and 16 years of age who have suffered physical abuse and neglect, as well as minors in residential care centers with other measures of protection. Most studies focus on the neurobiological consequences of the abuse, and mainly at an early age. However, there are very few studies that analyze the executive functions of victims of child abuse, while also taking into account the type of abuse suffered. This study aims to identify whether the consequences of child abuse for the executive functions are different for those minors who have been victims of physical abuse and neglect, in comparison with minors with other protective measures. The participants were 44 minors who had suffered child abuse and 24 minors with other protective measures, distinct from abuse. Three neuropsychological tests were used: (a) the Five Digits Test (FDT), (b) the Behavioral Assessment of the Dysexecutive Syndrome in Children (BADS-C), and (c) the Wechsler Intelligence Scale for Children?V (WISC-V). The results showed difficulties in those minors who had been victim of physical abuse and neglect, in their cognitive flexibility capabilities, inhibitory control, the ability to take decisions, the ability to organize and plan their behavior, control of emotions, and attention control. It was the minors who were victims of physical neglect that showed the greatest difficulties in their executive functions. The results of the study will permit us to design an educational intervention in the residential care centers that can encourage advances in the affected areas through the setting up of different strategies to favor the stimulation, reinforcement, and rehabilitation of the executive functions.